2016
DOI: 10.4103/1119-3077.178918
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic effect of diclofenac sodium administered via the epidural route in an experimental visceral pain model

Abstract: Single and repeated doses of diclofenac sodium via epidural route have an analgesic effect in a visceral pain model in rats without developing tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…It suggested that the central sensitization of rats is extremely obvious and rapid in the model of visceral pain induced by acetic acid, while nalbuphine could significantly inhibit this change. These experimental results are consistent with the data in other studies [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…It suggested that the central sensitization of rats is extremely obvious and rapid in the model of visceral pain induced by acetic acid, while nalbuphine could significantly inhibit this change. These experimental results are consistent with the data in other studies [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this research, the analgesic drug nalbuphine signi cantly decreased the writhing numbers of rats caused by acetic acid and the PWT. These experimental results are consistent with the data in other studies [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the number of writhes in a certain period re ects the degree of pain in rats and is often used in pain-model experiments [41][42][43]. Acute visceral pain like acute appendicitis tends to lead to super cial or deep hyperalgesia or allodynia [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After acupoint electroacupuncture treatment, the synthesis and utilization of norepinephrine is accelerated, but the utilization speed is faster than the synthesis speed [9].…”
Section: Introductionmentioning
confidence: 99%